Factors Influencing the Gut Microbiota, Inflammation, and Type 2 Diabetes - Wen, Li (J Nutr, 2017)
The gut microbiota is a complex community of bacteria residing in the intestine. Animal models have demonstrated that several factors contribute to and can significantly alter the composition of the gut microbiota, including genetics; the mode of delivery at birth; the method of infant feeding; the use of medications, especially antibiotics; and the diet. There may exist a gut microbiota signature that promotes intestinal inflammation and subsequent systemic low-grade inflammation, which in turn promotes the development of type 2 diabetes. There are preliminary studies that suggest that the consumption of probiotic bacteria such as those found in yogurt and other fermented milk products can beneficially alter the composition of the gut microbiome, which in turn changes the host metabolism. Obesity, insulin resistance, fatty liver disease, and low-grade peripheral inflammation are more prevalent in patients with low α diversity in the gut microbiome than they are in patients with high α diversity. Fermented milk products, such as yogurt, deliver a large number of lactic acid bacteria to the gastrointestinal tract. They may modify the intestinal environment, including inhibiting lipopolysaccharide production and increasing the tight junctions of gut epithelia cells.